Form Poetry Posterin Contem Porary Kurdish Poetry - Lect. Parween Abdullah khudhur; Prof. Dr. Fuad Rashid Mohammd (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
This research falls under the title " Form poetry posterin contem porary Kurdish poetry” which is trying to present the form of a "poetic poster" in Kurdish literature, and it applies a literary text in two main areas: form and content. In this research, he searches for the form of hair, which includes the form of long and short poetry. Historically, the Kurdish poetic form passed through several stages, and here we chose the short poetic form in the short poetic text. In terms of concepts, dialects and qualities, this research tried to display the most prominent pictorial scenes or poetic posters, with the selection of texts of pictorial scenes and the practice of the principles and recipes of poetic posters on some texts. The issues of the research were based on the principles and parts of the research. However, the results of the research will be indicated in the light of the study, and among the most prominent of these results, we found that the main point of the researches, poets in some texts could not fully implement the poetic posters.